The Development and Utilization of an Electronic Assessment Software in Dental Education: A Comprehensive Evaluation - Ali Al Ehaideb; Abdulmohsen Alfadley; Maryam A. Alghilan; Fathima F Farook; Nora Alhazmi; Elgene Castaneda; Fatimah Al Qarni; Muhammad Nadeem; Lubna Alkadi (Elsevier, 2024)
Purpose/Objectives: This article introduces the Key Electronic Assessment Platform (KEAP), an electronic-based assessment platform created in-house at the College of Dentistry (COD), King Saud bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh, Saudi Arabia. It highlights the platform's integral value and demand within the educational system. Methods: The article introduces the KEAP system design and architecture, describes its features, tests, and implementation in addition to its maintenance and security. It also presents the outcomes of KEAP utilization and the level of users' satisfaction. Results: The KEAP item bank has been expanded by more than 26,500 questions over the last four academic years and 1,255 exams have been administered. KEAP provides a highly secure structured framework for assessment planning, conduction, and evaluation. More than 90% of students and faculty are satisfied or very satisfied with their experience using the KEAP system indicating that it is well accepted by the end users. Conclusions: The development of KEAP is based on contextual factors in COD, KSAU-HS with the aim of creating a process for assessment that is valid, efficient, standardized, and highly secure. KEAP's design and successful implementation can provide a successful example of implementing electronic-based assessment in higher education.